Sonate pathétique: op. 13 dem Fürsten Carl Lichnowsky gewidmet [von] L. v. Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Braunschweig; C. Weinholtz; Germany, 2023)
Edition of the Piano Sonata no. 8 in C Minor, op. 13, published by C. Weinholtz as part of the collection of "Sonaten für das Pianoforte allein componirt von Louis van Beethoven;" issued separately with a list title page for two volumes containing 23 sonatas.